Open ecosystems expansion, competition, and predation shaped the evolution of Antilocapridae - Nascimento, João C S; Pires, Mathias M (Evolution, 2025)
Environmental changes and interactions with other groups can influence the balance between speciation and extinction within a clade. Disentangling those effects requires the use of adequate methods to characterize shifts in diversification rates in groups with rich diversification dynamics. Here, we analyze the diversification of a group of mammals with a single living member but a diverse past in North America, the Antilocapridae, to untangle the influence of environmental changes and biotic interactions in the clade’s evolutionary history. We found evidence consistent with an environmentally driven replacement within the family, where the most recent subfamily, Antilocaprinae, would have displaced the earliest subfamily, Merycodontinae. C4 grassland expansion seems to have increased the speciation rate within subfamily Antilocaprinae, indirectly contributing to an increase in extinction rates of the Merycodontinae. We also found that proboscideans could have contributed to the decline in Merycodontinae by suppressing speciation. Further, we show that the recent rise in extinction of antilocaprids may be associated with the diversification of Felinae, which includes modern and extinct predators of antilocaprids. More than uncovering the role of competition and predation in shaping the diversification of the clade, our results highlight the complex ways in which both the environment and biotic interactions may determine the fate of biological groups.